Effect of Yoga Breathing Exercises on Ventilatory Function - Banstola, Dinesh (Journal of Gandaki Medical College (Print), 2017)
Introduction: Controlled breathing not only keeps your mind and body functioning at their best, it can also lower blood pressure, promote feelings of calm and relaxation and help you de-stress. Many experts encourage using the yoga breathing exercises as a means of increasing awareness, mindfulness and reducing anxiety. Over-worked, under-slept, and feeling pressure may impair breathing pattern. There are some yoga breathing exercise techniques that improve ventilator function.Objective: To assess the effect of yoga breathing exercises on their ventilatory function. Methods: Forty eight male and female students of 18 - 30 years were involved in the study of ventilatory function before and after yoga breathing exercise. Pulmonary function tests were performed with the subject sitting in a comfortable chair. Initial recording of tidal volume, inspiratory capacity, inspiratory reserve volume, expiratory reserve volume, forced vital capacity, and timed vital capacity in one second were measured.Results: There was significant increase in inspiratory reserve volume, expiratory reserve volume, vital capacity, forced expiratory volume in one second and forced vital capacity after yoga breathing exercise.Conclusion: Yoga breathing exercise improves ventilatory function. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, page: 17-22